PENERAPAN MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 124 PEKANBARU - Ollyvia, Yollanda; Witri, Gustimal; N, Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research was mathematic learning outcomes in fourth grade (IV) students SD Negeri 124 Pekanbaru still low with average value 62,17 (with KKM 74). The purpose of this research was to improve mathematic learningoutcomes of the fourth grade (IV) students SD Negeri 124 Pekanbaru with the implementation of ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) learning model. This research was classroom action research with two cycles. Thesubjects were students of class IV SD Negeri 124 Pekanbaru academic years 2015/2016 which amounted to 30 people consisting of 16 women and 14 men. Based on the result adiscussion the observation of teacher’s and student activity sheet seen rising each meeting. Teacher’s activity with the implementation of ARIAS learning model at first meeting of first cycle was 75% (enough), and second meeting was 81,25% (good). At second cycle, teacher’s activity at first meeting was 89,58% (good) and second meeting was 95,83% (very good). Students activities at first meeting of first cycle was 66,67%(less) and second meeting was 70,83% (enough). At second cycle, students activities at first meeting was 83,33% (good), second meeting was 93,78% (very good). Mathematic learning outcomes before implementation ARIAS learning model average 62,17, after implementation of ARIAS learning model UH I was 72,50 that improve 16,61%, UH II was 85,17 that improve 36,99%. Implementation of ARIAS learning model canimproved mathematic learning outcomes of the fourth grade (IV) students SD Negeri 124 Pekanbaru.Key Words: ARIAS learning model, mathematic studies students achievement